A Proposed Biosynthetic Pathway of Picrosides Linked through the Detection of Biochemical Intermediates in the Endangered Medicinal Herb Picrorhiza kurroa. Issue 6 (21st May 2013) - Kumar, Varun; Sood, Hemant; Sharma, Manu; Chauhan, Rajinder Singh
ABSTRACT: Introduction: Picrorhiza kurroa Royle ex Benth is an important medicinal herb used in the preparation of several herbal drug formulations due to the presence of picroside‐I (P‐I) and picroside‐II (P‐II) along with other iridoid‐glucosides derivatives. Objective: The endangered status of P. kurroa coupled with lack of information on biosynthesis of P‐I and P‐II necessitate deciphering the biosynthetic pathway for picrosides. Methods: LC with electrospray ionisation (ESI) and quadrupole time of flight combined with MS/MS was used to detect intermediates and assemble the picrosides biosynthetic pathway in P. kurroa . Results: The presence of catalpol and aucubin, the major backbone structures of picrosides, along with intermediate metabolites boschnaloside, bartsioside and mussaenosidic acid, was confirmed in ESI negative mode with pseudomolecular ion peaks, that is, m/z 361, m/z 343, m/z 345, m/z 329 and m/z 375 ions and their fragmentation patterns. Conclusion: The picrosides biosynthetic pathway is expected to provide a reliable platform towards understanding the molecular components (genes/enzymes) of P‐I and P‐II biosynthesis in P. kurroa for their eventual utilisation in various applications. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : LC‐ESI‐MS/MS, was used to assemble the complete picrosides biosynthetic pathway in P. kurroa through the detection of catalpol and aucubin, two major backbone structures of picrosides along with intermediate metabolites; boschnaloside, bartsioside and mussaenosidic acid, which were confirmed in ESI‐negative mode with pseudo‐molecular ion peaks i.e. m/z 361, m/z 343, m/z 345, m/z 329 and m/z 375 ions and their fragmentation patterns.